IMPROVING THE STUDENTS’ LEARNING OUTCOMES IN THE CIVICS SUBJECTS THROUGH MIND MAPPING MODEL AT ELEMENTARY SCHOOL - Istiqomah, Endah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The research is aimed to describe the students’ learning outcomes in the Civics Subjects by using the Mind Mapping Model at 5th grade of SDN 19 Sungaitanang. The classroom-action research is conducted in the research by using both qualitative and quantitative approaches. The subjects of the research were the teacher and 22 students of the school. This research was conducted in two cycles where each cycle consists of planning, acting, observing, and reflecting. The result of the research shows that: a) the lesson plan increased from  73.21% (adequate) in cycle I to 92.85% (very good) in cycle II, b) in term of the teacher’s teaching aspect increased from 74.99% (adequate) in cycle I to 94.44% (very good) in cycle II; meanwhile, in the students’ learning aspect increased from 73.60% (adequate) in cycle I to 91.66% (very good) in cycle II, c) the students’ learning outcomes increased from 75.28 (adequate) in cycle I to 88.38 (very good) in cycle II. Thus, the use of Mind Mapping model has improved the students’ learning outcomes in learning the Civics Subjects at 5th Grade of SDN 19 Sungaitanang. Keywords:learning outcome; Civics; Mind Mapping